Extrapulmonary Small Cell Carcinoma of the Anal Canal: A Case Report and Review of the Literature - Joshua M. Eberhardt; Karen Brown; Shelly Lo; Suneel Nagda; Sherri Yong (Case Reports in Medicine)
Purpose. Extrapulmonary small cell carcinoma affecting the anal canal is a rare and poorly understood entity which can, in its early stages, masquerade as benign anorectal disease such as hemorrhoids. Methods. We report a case of this rare malignancy which initially presented with hematochezia and anal pain. We also review the literature with regard to previously described cases and management strategies including the role of surgery. Results. Despite aggressive multidisciplinary treatment consisting of chemotherapy and radiation, the disease progressed rapidly with dissemination occurring only three months after completion of treatment. Because of the aggressive nature of this tumor, the treatment options for this almost universally fatal malignancy are often palliative in nature. Conclusion. Chemoradiotherapy is likely the most reasonable approach to extrapulmonary small cell carcinoma of the anal canal given its aggressiveness.